2006
DOI: 10.1042/bj20051213
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of the three Snf1-activating kinases of Saccharomyces cerevisiae

Abstract: Members of the Snf1/AMPK family of protein kinases are activated by distinct upstream kinases that phosphorylate a conserved threonine residue in the Snf1/AMPK activation loop. Recently, the identities of the Snf1- and AMPK-activating kinases have been determined. Here we describe the purification and characterization of the three Snf1-activating kinases of Saccharomyces cerevisiae. The identities of proteins associated with the Snf1-activating kinases were determined by peptide mass fingerprinting. These kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 43 publications
3
80
0
1
Order By: Relevance
“…The GST-tagged Snf1 kinase domain was purified from bacterial cells by affinity chromatography (21). The cDNA for human protein phosphatase (PP) 2C␣ was purchased from Open Biosystems (IHS1382-8646531) and inserted into the bacterial expression plasmid pET14b (Novagen).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The GST-tagged Snf1 kinase domain was purified from bacterial cells by affinity chromatography (21). The cDNA for human protein phosphatase (PP) 2C␣ was purchased from Open Biosystems (IHS1382-8646531) and inserted into the bacterial expression plasmid pET14b (Novagen).…”
Section: Methodsmentioning
confidence: 99%
“…Rabbit PP1 was purchased from Sigma (P7937). Yeast Glc7 was TAP-purified as described (21). Human AMPK composed of the ␣ 1 , ␤ 1 , and ␥ 1 subunits was purified as described (22).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the protein kinases Sak1, Tos3, and Elm1 phosphorylates SNF1 in vivo (5,7). Sak1 is the primary upstream kinase (8,(51)(52)(53), and its C-terminal region interacts with the Snf1 kinase domain (43). To assess the role of the heterotrimer in determining interactions with activating kinases in vivo, we examined phosphorylation of Snf1(1-309).…”
Section: Mutations That Cause Phosphorylation Of the Heterotrimer Duringmentioning
confidence: 99%
“…The Snf1p kinase is required for pseudohyphal growth and for growth on secondary carbon sources (23)(24)(25). Snf1p is regulated by the kinase Sak1p during nitrogen signaling, and Snf1p pairs with its Gal83p ␤-subunit isoform to activate expression of downstream targets that enable pseudohyphal growth (26,27). Recent genomic studies have identified additional signaling pathways and gene sets that contribute to yeast pseudohyphal growth (28 -31), collectively indicating an extensive regulatory network controlling gene and protein activity during the filamentous growth transition.…”
mentioning
confidence: 99%